Consumer Protection in TikTok Shop Sale Transactions Based on Law Number 8 of 1999 - Defriza, Rita (JUSTISI, 2025)
Online shopping transactions using the TikTok Shop media often experience problems and poor service quality from the business actors. It is because they commonly commit fraud in online shopping with the TikTok Shop media. It is due to the absence of a direct meeting between the seller and the buyer, the size and color of the goods purchased do not match, the dishonesty of the business actors about the goods being sold, and the consumer's lack of understanding of the details of the product ordered. For this reason, consumer rights must be protected by the provisions of laws and regulations. This study analyses consumer protection in online shopping transactions through the TikTok Shop media based on Law Number 8 of 1999 and Law Number 1 of 2024. This study used empirical jurisprudence with a sociological normative approach. The type of data used is primary data. The results of the study indicate that there are aspects of legal protection for online consumers, as shown by Consumer Protection Law Number 8 of 1999 and Electronic Information and Transactions Law (ITE) Number 11 of 2008. The law provides fundamental rights for consumers, such as the right to security, accurate information, and compensation for non-conforming products. The results indicate the importance of implementing the principles of transparency and responsibility among online business actors to prevent consumer losses. Adequate consumer protection can increase consumer trust in e-commerce and encourage business actors to be more responsible in running their businesses.